Additional analyses exploring the hypothesized transdifferentiation of plasmablasts to developing neutrophils in severe COVID-19 - Wilk, Aaron J; Rustagi, Arjun; Zhao, Nancy Q; Martin, Beth A; Rogers, Angela J; Blish, Catherine A (bioRxiv, 2020)
Abstract We thank Alquicira-Hernandez et al. for their reanalysis of our single-cell transcriptomic dataset profiling peripheral immune responses to severe COVID-19. We agree that careful analysis of single-cell sequencing data is important for generating cogent hypotheses but find several aspects of their criticism of our analysis to be problematic. Here we respond briefly to misunderstandings and inaccuracies in their commentary that may have led to misinformed interpretation of our results. Competing Interest Statement The authors have declared no competing interest.